Project Team in Project Management Methodologies - Peszko, Agnieszka (Decision Making in Manufacturing and Services, 2021)
The specific nature of project management causes that the selection of the right people to join the project team has become crucial to the success of any project. The present study aims at showing the role of a well-chosen project team in the project management regardless of whether the project is run according to traditional or agile methodologies. Special attention has been paid to the decision making process in project team with the use of traditional and agile methodologies. In case of traditional, classical methodologies, more efficient are teams of highly qualified specialists, which are able to make decisions, more often individual ones, as quickly as possible and precisely. Given the fact that in agile methodologies there is greater decisiveness of the team, group decisions are made more often. Management’s confidence in project team is of vital importance in agile methodologies. In order to fulfill the aim of the study, traditional and agile methodologies for project management have been briefly characterized, the process of project team building and the results of scientific research pointing to significant role of the project team in project management have been presented. It has been stressed out that, regardless of the chosen methodology, while selecting project team members it is important to consider not only members’ knowledge or experience, but also relevant personality traits and interpersonal skills (social skills). However, it should be pointed out that given the specific nature of the agile methodologies, social skills of team members become incredibly important, and in many cases more important than professional competences.